수화 시의 형태학적 특징에 따른 건해삼의 등급 분류 시스템 개발 - 이충욱(Choong Uk Lee); 윤원병(Won Byong Yoon) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Image analysis and k-mean clustering were conducted to develop a grading system of dried sea cucumber (SC) based on rehydration rate. The SC images were obtained by taking pictures in a box under controlled light conditions. The region of interest was extracted to depict the shape of the SC in a 2D graph, and those 2D shapes were rendered to build a 3D model. The results from the image analysis provided the morphological features of the SC, including length, width, surface area, and volume, to obtain the parameters of the k-mean clustering weight. The k-mean clustering classified the SC samples into three different grades. Each SC sample was rehydrated at $30^{°}C$ for 40 h. During rehydration, the flux of each grade was analyzed. Our study demonstrates that the mass transfer rate of SC increased as the surface area increased, and the grade of SC was classified based on rehydration rate. This study suggests that the optimal rehydration process for SC can be achieved by applying a suitable grading system. 본 연구에서는 건해삼의 수화도에 따른 등급 분류를 확립하고자 하였다. 건해삼은 영상분석을 통하여 건해삼의 길이, 너비, 부피, 겉넓이의 형태학적 특징을 추출하였다. 측정된 data를 이용하여 k-mean clustering을 실시, 95개의 건해삼을 3개의 등급으로 분류하여 $30^{°}C$에서 40시간 수화실험을 실시하였다. 건해삼의 k-mean clustering을 실시한 결과 건해삼의 부피와 겉넓이는 건해삼의 등급을 가장 잘 나타낼 수 있는 인자였다. 등급별 수분 함량은 grade1은 71.23%, grade2는 75.60%, grade3는 85.62%를 확인하였다. 본 수화속도의 차이는 등급별 해삼이 동일한 수화 flux를 갖는 것을 고려하였을 때, 해삼의 수화는 겉넓이에 지배적임을 확인할 수 있다. 해삼의 수화는 물의 물질전달을 통해 이루어지며 Fick의 확산법칙에 따라 겉넓이가 커질수록 물질전달 속도가 증가함을 본 연구의 수화실험 결과에서도 확인할 수 있었다. 본 연구에서는 건해삼의 등급을 분류하여 최적의 수분 함량(75%)을 충족하기 위한 등급별 수화시간을 도출하였다. 본 연구에서 도출된 건해삼의 등급판별은 "수화도에 따른 건해삼의 품질 변화"에 대한 추가적인 연구를 통해 등급별 최적의 수화시간의 도출이 가능하다.